Mountain Tourism and Nepal’s Mountain Tourism Policy: An Overview - Sherpa, Ang Tshering; Shrestha, Hari Prasad (PYC Nepal Journal of Management, 2011)
Nepal is a prime tourist destination for many due to its natural scenic beauty, the world's highest snow-topped mountain peaks of Himalayas, beautiful lakes, flora and fauna, biodiversity, and rich cultural, religious and archeological heritage. As such, the tourism industry in the country is growing at a fast pace and making significant contribution to the national economy. The history reveals that tourism in Nepal began with mountain tourism. Mountain tourism has many different aspects and the most important ones of which are mountaineering expeditions and trekking. Every year, great many tourists all over the world come to the country of Mt. Everest for expeditions and trekking purposes. Although the scope of whole mountain tourism development in Nepal is very high, this paper is particularly concerned with the development of mountaineering expeditions and trekking. It is obvious that mountain tourism development needs proper government plans and policies and the enthused participation the private escort as well. However, the tourism experts have pointed out the poor track record of implementing government plans and policies has not developed mountain tourism as desired and expected. The reasons have been attributed to unstable politics, lack of vision and expertise, and lack of concerted and coordinated efforts from all the quarters concerned. Despite the new Tourism Policy, 2008 (2065 BS) has come into implementation; adequate focus on mountain tourism is still missing. The stumbling blocks in the development of mountain tourism must be removed to make Nepal the prime destination for mountaineering expeditions and trekking. For developing mountain tourism and having sustainable competitive edge over other competing countries in this sector of tourism, the paper offers some important measures as suggestions.